(untitled) (Fiep Bulletin - online, 2013)
After founding of the city of Bethlehem (from the fort’s corner in 1616), the land of the Rio Negro became the target of expeditions that brought soldiers and missionaries. The fort, which led to the city of Manaus was built in 1669 and was named the Fort of Sao Jose da Barra in Rio Negro. The constructions of fort brand also the arrival of "civilization", a culture that is needed and that, after time, determine the habits of the city. The Bar’s place is slowly changing in this provincial period. It was a city built for a specific group, to suit the taste prevailing at the time, looking up, with it, erase the image of town indigene. Appropriated less is the use of space much of the population. The period from 1920 to 1967 is considered by many historians as the period of the city in crisis. Manaus was living the end of the cycle of rubber, in the period before the installation of the free zone. People also had their ways and customs adapted to the richness of the period. The port, in the staircase of Remedios, was the arrival point for many people from the interior to the capital. This mark today is with the interference, sometimes no scruple public places and in their works. The removal and placement of objects from one place to another is a characteristic not only of our city; but the city has modernized and press by this delay. The lack of care for the works and monuments reflects the carelessness with the history and the memory of the city.